PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN BOARD SIZE TERHADAP KECEPATAN PENYESUAIAN STRUKTUR MODAL: A SYSTEMATIC LITERATURE REVIEW - Hamami Fildzah Fataqun; Totok Dewayanto (Diponegoro Journal of Accounting, 2025)
Establishing an optimal capital structure is essential for firms to maximize value and enhance funding efficiency. However, numerous factors, such as firm-specific characteristics and corporate governance mechanisms, affect how quickly firms adjust their capital structure toward target leverage. Therefore, this study aims to analyze the contribution of these key variables to the adjustment process. This research employs a systematic literature review by analyzing various article published in the Scopus database between 2020 and 2024. The research stages included identification, selection, and synthesis of findings to provide a comprehensive understanding of the relationships between variables. The results indicate that profitability generally impacts capital structure adjustment speed, firm size shows mixed effects, and larger boards tend to accelerate capital structure adjustment. These findings highlight the complexity of capital structure dynamics, influenced by firm-specific characteristics and corporate governance mechanism.  This study contributes academically by synthesizing prior research findings and recommending the need for an empirical approach in capital structure decision-making.